Molecular modifications to mitigate oxidative stress and improve red blood cell storability - Anastasiadi, Alkmini T.; Stamoulis, Konstantinos; Kriebardis, Anastasios G.; Tzounakas, Vassilis L. (Frontiers in Physiology, 2024)
The development of red blood cell (RBC) storage lesion during hypothermic storage has long posed challenges for blood transfusion efficacy. These alterations are primarily driven by oxidative stress, concern both structural and biochemical aspects of RBCs, and affect their interactions with the recipient’s tissues post-transfusion. Efforts to counteract these effects focus on improving the antioxidant capacity within stored RBCs, reducing oxygen exposure, and scavenging harmful molecules that accumulate during storage. Various supplements, such as ascorbic acid, N-acetylcysteine, polyphenolic compounds, and specific metabolites have shown the potential to improve RBC quality by reducing oxidative lesions and lysis phenomena, and enhancing antioxidant, energy, or proteostasis networks. Accordingly, anaerobic storage has emerged as a promising strategy, demonstrating improved RBC storability and recovery in both animal models and preliminary human studies. Finally, targeted scavenging of harmful storage-related phenotypes and molecules, like removal signals, oxidized proteins, and extracellular hemoglobin, while not so studied, also has the potential to benefit both the unit and the patient in need. Omics technologies have aided a lot in these endeavors by revealing biomarkers of superior storability and, thus, potential novel supplementation strategies. Nonetheless, while the so far examined storage modifications show significant promise, there are not many post-transfusion studies (either in vitro, in animal models, or humans) to evaluate RBC efficacy in the transfusion setting. Looking ahead, the future of blood storage and transfusion will likely depend on the optimization of these interventions to extend the shelf-life and quality of stored RBCs, as well as their therapeutic outcome.